Nilai-Nilai Kearifan Lokal Patrol Sahur Ramadan di Desa Kademangan Kecamatan Pagelaran Kabupaten Malang - Haniyah Kamilah Az-Zahra; Daroe Iswatiningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the importance of preserving local wisdom amid the flow of modernization that influences community life, particularly in the tradition of Ramadan Sahur Patrol in Kademangan Village, Pagelaran District, Malang Regency. This research aims to describe the implementation of the sahur patrol, identify the local wisdom values embedded within it, and analyze community responses to the tradition. The method used is qualitative with a cultural anthropology approach and a descriptive research design. Data were collected through interviews and documentation involving purposively selected informants, including community leaders, patrol participants, and local government officials. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that the sahur patrol is carried out in a structured manner by utilizing traditional musical instruments, involving cross-generational participation, and being integrated with the community’s religious activities. This tradition contains religious, social, educational, cultural, mutual cooperation, togetherness, and responsibility values. In addition, the community shows a highly positive response through active participation and support for the sustainability of the tradition. The implications of this study emphasize that the sahur patrol plays an important role as a medium for cultural preservation, strengthening social solidarity, and forming collective identity and character within the community.